2008
DOI: 10.3989/gya.2008.v59.i1.488
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different technological co-adjuvants on the quality and yield of virgin olive oil using response surfaces methodology

Abstract: RESUMENInfluencia de diferentes coadyuvantes tecnológicos en la calidad y rendimiento del aceite de oliva virgen utilizando la metodología de superficies de respuesta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…However, these findings were not in agreement with the results of García et al (2005), Fernández-Valdivia et al (2008, Moya et al (2010), Carrapiso et al (2013), and Caponio et al (2014, who concluded that processing aids such as hot water dipping, talc, and micro talc did not affect free fatty acids. Canamasas and Ravetti, (2014) found that oil extracted with Talc (2.0%) and microtalc had the lower acidity (free fatty acid) than the control.…”
Section: Free Aciditycontrasting
confidence: 67%
See 1 more Smart Citation
“…However, these findings were not in agreement with the results of García et al (2005), Fernández-Valdivia et al (2008, Moya et al (2010), Carrapiso et al (2013), and Caponio et al (2014, who concluded that processing aids such as hot water dipping, talc, and micro talc did not affect free fatty acids. Canamasas and Ravetti, (2014) found that oil extracted with Talc (2.0%) and microtalc had the lower acidity (free fatty acid) than the control.…”
Section: Free Aciditycontrasting
confidence: 67%
“…It has been reported that most olive oil-producing countries (such as Spain and Italy) have utilized processing aids (co-adjuvant agents and techniques) to improve oil extraction efficiency (up to 10 to 30%) and to reduce the loss in oil in pomace (García et al, 2005;Cruz et al, 2007;Canamasas and Ravetti, 2011). Although talc and micronized talc powder (Fernández-Valdivia et al, 2008), specific enzymes (Sharma and Sharma, 2007;Najafian et al, 2009), common salt (NaCl, KCl), calcium carbonate (Espínola et al, 2009) and hot water dipping (García et al, 2005;Al-Rousan, 2017), as processing aids and techniques, have been commonly applied in the olive oil industry, nowadays, in Europe, only the use of hydrate magnesium silicate (natural talc) and kaolinitic clays are permitted (Vidal et al, 2018). Generally, these aids have improved oil extractability from the olive paste by breaking down the oil-water emulsion (Sadkaoui et al, 2016).…”
Section: Introductionmentioning
confidence: 99%